The Promise of Anti-idiotype Revisited - Kohler, Heinz; Pashov, Anastas; Kieber-Emmons, Thomas (Frontiers in Immunology, 2019)
The promise of idiotype-based therapeutics has been disappointing forcing a new look at the concept and its potential to generate an effective approach for immunotherapy. Here, the idiotype network theory is revisited with regard to the development of efficacious anti-idiotype vaccines. The experience of polyclonal anti-Idiotype reagents in animal models as well as an understanding of the immune response in humans lends to the proposition that polyclonal anti-Idiotype vaccines will be more effective compared to monoclonal-based anti-Idiotype vaccines. This novel strategy can be adapted in Biotech-standard production of therapeutic antibodies